2021
DOI: 10.1101/2021.07.23.453525
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Insights on the historical biogeography of Philippine native pigs and its relationship with Continental domestic and wild boars

Abstract: The Philippine archipelago was believed to have never been connected to the Asian continent, even during the severe Quaternary sea-level drops. As a result, the history of pig dispersal in the Philippines remains controversial and must have some anthropogenic origin associated with some human migration events. In this study, the context of origin, dispersal, and the level of genetic introgression in Philippine native pigs were deduced using mitochondrial DNA D-loop analysis altogether with domestic pigs and wi… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 71 publications
(90 reference statements)
0
3
0
Order By: Relevance
“…Based on the patterns of mutational signatures, the most numerous haplotypes (20 haplotypes; n = 103/184, 55.98%) in our dataset which covered the largest area, formed an independent clade although this haplogroup was not present in Northern Luzon. While this study is the first analysis to resolve the complete mtDNA D-loop of a substantial number of sequences from these populations, it shows that it has an analogous signature to the previously documented haplogroup in MSEA, which was classified as D7 based on short/partial fragment analysis (510 bp) ( Tanaka et al, 2008 ; Layos et al, 2021 ). Using complete D-loop fragment analysis, we confirmed that this haplogroup is distinct from the available haplogroup that has been tentatively classified by haplogroup-specific motif recognition in porcine mtDNA ( Larson et al, 2005 ; Wu et al, 2007 ).…”
Section: Resultsmentioning
confidence: 66%
See 2 more Smart Citations
“…Based on the patterns of mutational signatures, the most numerous haplotypes (20 haplotypes; n = 103/184, 55.98%) in our dataset which covered the largest area, formed an independent clade although this haplogroup was not present in Northern Luzon. While this study is the first analysis to resolve the complete mtDNA D-loop of a substantial number of sequences from these populations, it shows that it has an analogous signature to the previously documented haplogroup in MSEA, which was classified as D7 based on short/partial fragment analysis (510 bp) ( Tanaka et al, 2008 ; Layos et al, 2021 ). Using complete D-loop fragment analysis, we confirmed that this haplogroup is distinct from the available haplogroup that has been tentatively classified by haplogroup-specific motif recognition in porcine mtDNA ( Larson et al, 2005 ; Wu et al, 2007 ).…”
Section: Resultsmentioning
confidence: 66%
“…By screening and detecting the haplogroup-specific mutational motifs, we assigned each haplotype based on the smallest named sub-phylo groups to which it belongs. Recently, it has been proposed that the six major clusters of porcine mtDNA sequences, designated D1 to D6 ( Larson et al, 2005 ), with the addition of D7 (previously designated MTSEA, which is thought to be restricted to the Indo-Burma Biodiversity Hotspots (IBBH); Tanaka et al, 2008 ; Larson et al, 2010 ; Layos et al, 2021 ) reflect domestication from genetically distinct subpopulations of wild boars ( Supplementary Table S3 ). Our results showed that the D-loop sequences of Philippine pigs obtained in this study could be classified into five phylogenetically distinct haplogroups such as D1, D2, D6, D7, and Lanyu Clade, except for the Philippine wild pig haplotypes (PHL44-47).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation